Wild whale faecal samples as a proxy of anthropogenic impact - Marianna Marangi (Nature Portfolio, 2021)
Abstract The occurrence of protozoan parasite, bacterial communities, organic pollutants and heavy metals was investigated in free-ranging species of fin (Balaenoptera physalus, n. 2) and sperm (Physeter macrocephalus, n. 2) whales from the Pelagos Sanctuary, Corsican-Ligurian Provencal Basin (Northern-Western Mediterranean Sea). Out of four faecal samples investigated, two from fin whales and one from sperm whale were found positive to Blastocystis sp. A higher number of sequences related to Synergistetes and Spirochaetae were found in sperm whales if compared with fin whales. Moreover, As, Co and Hg were found exclusively in sperm whale faecal samples, while Pb was found only in fin whale faecal samples. The concentration of both PAH and PCB was always below the limit of detection. This is the first report in which the presence of these opportunistic pathogens, bacteria and chemical pollutants have been investigated in faecal samples of free-ranging whale species and the first record of Blastocystis in fin and sperm whales. Thus, this study may provide baseline data on new anthropozoonotic parasite, bacterial records and heavy metals in free-ranging fin and sperm whales, probably as a result of an increasing anthropogenic activity. This survey calls for more integrated research to perform regular monitoring programs supported by national and/or international authorities responsible for preservation of these still vulnerable and threatened whale species in the Mediterranean Sea.